Google Sheet-based Monitoring of Screw Turbine Pico Hydro Power Plant on Masangan Wetan Village's River Flow - Wildan Arief Prasetyo; Arief Wisaksono; Indah Sulistiyowati (Procedia of Engineering and Life Science, 2022)
Developments continue to be made to meet the electricity needs of the people in Indonesia. Still, in dire need of electricity as a life support, the Pico hydro Power Plant (PLTPH) is a cheap alternative, the advantage of the water turbine is that it is environmentally friendly because it does not disturb the water ecosystem in the rivers that exist in every rural area. The method used by the author is to design a tool to measure the rotation of the generator, the power that comes out of the generator, and others. where the flow of water passes through the turbine lattice so that it moves the turbine shaft and produces electrical energy through a generator then electricity can be stored in the battery and can be used for the appropriate working voltage of 12VDC. In the charging process, reading is also carried out by the sensor, to detect the voltage and current which is then processed by the NodeMCU Esp 32 and then transmitted into the Google sheet.